Smart Voting System Using Deep Learning and Computer Vision - Chekkera Anuhya,; C. Yamini, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper introduces a groundbreaking online voting system for Indian elections. The model emphasizes enhanced security by requiring voters to confirm their high-security passwords before their votes are recorded in the Election Commission of India's main database. A standout feature of this system is that voters can verify whether their vote has been cast for the correct candidate or party. Additionally, it allows individuals to vote from outside their designated constituency or from a location of their choice. With this proposed system, the vote tallying process will be automated, significantly reducing the time needed and enabling the Election Commissioner of India to announce results in a much shorter timeframe.
Keywords: Voting; Online; Computer Vision; Deep Learning; Haarcascading; OpenCV; OTP